2022
DOI: 10.1101/2022.05.19.22272842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-World Effectiveness of Casirivimab and Imdevimab Among Patients Diagnosed With COVID-19 in the Ambulatory Setting: A Retrospective Cohort Study Using a Large Claims Database

Abstract: ImportanceData on real-world effectiveness of casirivimab and imdevimab (CAS+IMD) for treatment of coronavirus 2019 (COVID-19) are limited, especially with regard to variants of concern such as Delta.ObjectiveTo assess effectiveness of CAS+IMD versus no COVID-19 antibody treatment among patients diagnosed with COVID-19 in the ambulatory setting overall and among subgroups, including patients diagnosed during the Delta-dominant period prior to Omicron emergence.DesignRetrospective cohort study.SettingKomodo Hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…While the hospitalization outcome of that study was for any cause, it also evaluated IV CAS+IMD and suggested no significant difference in outcomes between IV and SC administration. The results are also consistent with real-world effectiveness reported in claims-based analyses, including one that encompassed a period when the Delta variant was dominant, although SC administration was not specifically evaluated [ 25 , 29 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While the hospitalization outcome of that study was for any cause, it also evaluated IV CAS+IMD and suggested no significant difference in outcomes between IV and SC administration. The results are also consistent with real-world effectiveness reported in claims-based analyses, including one that encompassed a period when the Delta variant was dominant, although SC administration was not specifically evaluated [ 25 , 29 ].…”
Section: Discussionsupporting
confidence: 78%
“…We conducted a retrospective cohort study using closed administrative claims data from the Komodo Health claims database [ 25 ]. Komodo health data is a real-world dataset which integrates various sources of patient-level data to map longitudinal patient journeys.…”
Section: Methodsmentioning
confidence: 99%
“…The results are also consistent with real-world effectiveness reported in claims-based analyses, including one that encompassed a period when the Delta variant was dominant, although SC administration was not specifically evaluated. 25, 29…”
Section: Discussionmentioning
confidence: 99%
“…38, 39 However, given the limited number of patients with primary B-cell deficiencies, the benefit of treatment could not be confirmed in this subgroup, although prior real-world studies have demonstrated that this patient subgroup also benefits from CAS+IMD treatment. 25, 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation